A comparative study between amoxicillin + clavulanic acid and levofloxacin in the management of acute maxillary sinusitis at RIMS, Ranchi - Kumar, Sandeep; kumari, Abha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Acute rhinosinusitis is an acute viral or bacterial in which there is inflammation of the mucosa of the nose and paranasal sinuses. The aim of study was to compare the efficacy of oral amoxicillin-clavulanate with levofloxacin in the management of acute maxillary sinusitis. Methods: The present prospective study was conducted in the Department of ENT, Rajendra Institute of Medical Sciences, Ranchi during a period of 8 months i.e. from July 2016 to June 2017. In Group I patients 1 gm of amoxicillin-clavulanate was given two times a day and in Group II, 500 mg of Levofloxicin was given once a day for a period of 10 days. Patient’s complete demographic details were recorded including name, age and gender. Xylometazoline nasal spray and steam inhalations were given to all the patients. Results: The mean age of the subjects was 36.43±6.43 years. In both the groups, majority of the subjects were between 36-45 years of age. There were 34.7% (52) in Group I and 38.7% (n=58) in Group II who belonged to this age group. Least number of subjects was those aged more than 48 years. There were 88% subjects (n=132) in group I and 86% (n=129) subjects in Group II in whom complete resolution of symptoms was seen. Conclusions: From the above study we can conclude that both amoxicillin–clavulanic acid and levofloxacin are equally efficacious in managing cases of acute sinusitis. In this study there was no difference in the rate and duration of resolution amongst both the groups.